KEKUATAN HUKUM AKTA PENGANGKATAN ANAK YANG DIBUAT DIHADAPAN NOTARIS SESUDAH BERLAKUNYA PERATURAN PEMERINTAH NOMOR 54 TAHUN 2007 TENTANG PELAKSANAAN PENGANGKATAN ANAK - DEASY EVI PHANI TOGATOROP (PREMISE LAW JURNAL, 2017)
Before PP (Government Regulation) No. 54/2007 on the Implementation of Child Adoption was in effect, a Notary played his role in drawing up Child Adoption Certificate. At that time, child adoption was legal when there was a Notarial Deed. The reasearch shows after PP No. 54/2007 An Adoption Certificate which was made by a Notary before PP No. 54/2007 was in effect is valid and it is final and conclusive for those who made it before a Notary. This is in accordance with the transitional provision which states that by the time this PP is in effect all regulations on adoption are valid as far as they are not contrary to the PP. The role of a Notary in drawing up Adoption Certificate after PP No. 54/2007 is in effect is providing counseling and consultation for those who are involved in child adoption in order that people get information and understand the requirements and   procedure of child adoption. A Notary should refer to legal provisions which are related to the making of the law. Keywords: Legal Force, Certificate, Child Adoption, Notary